Micro RNA based cancer screening by blood test: a review - Salim, Bindu; Kandaswamy, A; MV, Athira; Vijayakumar, Madhulika; R, Adityan (Public Health Review: International Journal of Public Health Research, 2018)
Context: Circulating microRNA (miRNA) is of great importance to thebiomarker basednon-invasive cancer diagnosis. Objective: To identify circulating biomarkers for cancer screening and its usability with a micro fluidic device for developing an easy to use, cost effective screening tool by way of a blood test. Method: Reviewed published literature for expression of onco-miRNAs and miR-21(microRNA-21) in cancer patients’ serum and their detection methods. Results: miR-21 was chosen as circulating biomarker for breast cancer screening and testeda microfluidic device for breast cancer with 21 breast cancer and 30 healthy volunteers’ blood samples, results concurred with qPCR, the gold standard for quantification. Conclusion: In comparison to mammogram, which is the gold standard for breast cancer screening, microfluidic platform-based blood test for screening can reach a large population at affordable cost.